Does Conflict Disrupt Economic Growth in South Asia? - Abdul Rasheed, Sithy Jesmy (2016)
Several South Asian countries, namely Bangladesh, India, Nepal, Pakistan and Sri Lanka have experienced numerous internal as well as external armed-conflicts. Due to ongoing conflicts and militarization, military spending and the cost of conflict have increased drastically in South Asia. The direct and indirect causes of armed-conflict posing to be major threats to growth of national output in this region. This study examines the impact of conflict on economic growth in conflict affected South Asian region for the period 1980-2014 by employing the Solow growth model and Autoregressive Distributed Lag (ARDL) bounds test approach to cointegration. Prior to the estimation of cointegration, test to confirm evidence of long-run equilibrium relationship, unit root test and diagnostic tests were performed. The results of this study clearly suggest that armed conflict significantly contribute in decreasing per capita GDP in all countries in South Asia. Therefore, it is highly recommended that policy makers and government in respective countries should adopt constructive policies to prevent and control all possible internal and external conflicts. Ending conflict undoubtedly leads to minimize cost of conflict and supports opens the ways to enhancing output in South Asia.